Tree Growth Rings in Tropical Peat Swamp Forests of Kalimantan, Indonesia - Martin Worbes (Forests, 2017)
Tree growth rings are signs of the seasonality of tree growth and indicate how tree productivity relates to environmental factors. We studied the periodicity of tree growth ring formation in seasonally inundated peatlands of Central Kalimantan (southern Borneo), Indonesia. We collected samples from 47 individuals encompassing 27 tree species. About 40% of these species form distinct growth zones, 30% form indistinct ones, and the others were classified as in between. Radiocarbon age datings of single distinct growth zones (or “rings”) of two species showing very distinct rings, Horsfieldia crassifolia and Diospyros evena, confirm annual growth periodicity for the former; the latter forms rings in intervals of more than one year. The differences can be explained with species-specific sensitivity to the variable intensity of dry periods. The anatomical feature behind annual rings in Horsfieldia is the formation of marginal parenchyma bands. Tree ring curves of other investigated species with the same anatomical feature from the site show a good congruence with the curves from H. crassifolia. They can therefore be used as indicator species for growth rate estimations in environments with weak seasonality. The investigated peatland species show low annual growth increments compared to other tropical forests.